# Formula transformation

Is it possible to transform this equation to give R? $$y=x\left[\frac{\left(1+\frac{R}{12}\right)^{12\times{25}}}{\frac{R}{12}}-1\right]$$

-
I've edited your question. Please check whether it is what you meant to write. I appreciated your handwork, but please use LaTeX in future :) – Johnny Westerling Oct 9 '12 at 10:06
For some basic information about writing math at this site see e.g. here, here, here and here. – Américo Tavares Oct 9 '12 at 10:21
– Henry Oct 9 '12 at 11:37

Letting $w = \frac y x + 1$ and $r = \frac R {12}$, we are left with inverting $$w = \frac {(1+r)^{300}} r$$ $$w = \frac {(1+r)^{300}} {(r^{1/300})^{300}}$$ $$w^{1/300} = r^{-1/300} + r^{299/300}$$ Letting $z = r^{1/300}$ and multiplying by $z$ we have $$z^{300} - w^{1/300}z + 1 = 0$$
This is a trinomial equation of degree 300 in a form similar to Glasser's form, which you can read about here. (You can get Glasser's form exactly by substituting $z$ with $cz$ with an appropriate constant $c$, dependent on $w$ of course.)
You could rewrite like $\frac{R}{12}\left(\frac yx+1\right)-\sum_{k=0}^{12\times 25}\binom{12\times 25}{k}\left(\frac R{12}\right)^k=0$, but to my knownledge, there is no general way to solve that other than numerical.